Pharmacokinetics of Angiotensin-Converting Enzyme Inhibitors in Elderly Patients with Arterial Hypertension - Mikhailova, Elizaveta; Chernus, Natalya; Egorova, Elena; Lozano, Roberto (Bangladesh Journal of Medical Science, 2022)
Objective: With the gradual aging of the world’s population, selecting an effective treatment regime for arterial hypertension (AH) becomes increasingly important. This article aims to analyze the pharmacokinetic and pharmacodynamic properties of parent enalapril and generic drugs in elderly patients suffering from AH. Materials and methods: The study is randomized, implying random distribution of patients into study groups. The study was conducted in 2018 among 200 patients diagnosed with AH. All elderly patients (mean age 77.5 ± 1.5 years) were divided into two equal groups. Group 1 was prescribed 10 mg of original enalapril orally, and Group 2 similarly took 10 mg of generic enalapril. The blood pressure of all patients was measured 1, 2, 4, 6, 8, and 11 hours after dosing and one day after treatment. Also, blood samples were taken after blood pressure measurements. Results and Discussion: After 1 hour, differences between Groups 1 and 2 (p ≤ 0.001) were found at the level of 29.84 ng/1 ml for the original drug and 19.01 ng/1 ml for the generic. Further, these values were 38.2 ng/1 ml vs. 28.7 ng/1 ml (p ≤ 0.001) after 2 hours, 36.6 ng/1 ml vs. 26.5 ng/1 ml (p ≤ 0.001) after 4 hours, and 9.2 ng/1 ml vs 5.1 ng/1 ml (p ≤ 0.001) after 24 hours, respectively. The maximum concentration-time curve values for both medications corresponded to the period of 2 hours after administration. Conclusion:Thus, generics are much less effective as an antihypotensive medication than the original enalapril. Bangladesh Journal of Medical Science Vol. 21 No. 03 July’22 Page: 562-569